2006
DOI: 10.1590/s0103-50532006000500025
|View full text |Cite
|
Sign up to set email alerts
|

Sistematic study of benzo[a]pyrene in coffee samples

Abstract: Neste trabalho foi avaliado e otimizado um método para extração e quantificação de benzo [a]pireno (B[a]P) em amostras de café das espécies conillon (Coffea canephora) e arabica (Coffea arabica), verde e torrado em pó. A influência do processo de torração na formação do B[a]P também foi estudada. Estas amostras foram extraídas com acetona, seguidas por saponificação, extração com ciclohexano e purificação em coluna de silica-gel. A quantificação foi feita por CLAE por eluição isocrática em fase reversa com det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 4 publications
(6 reference statements)
1
15
0
5
Order By: Relevance
“…1 Thus, variable levels of PAHs have been reported in different food categories and beverages including vegetables and fruits, cereals, oils and fats, smoked products, coffee and tea. [2][3][4][5][6][7][8][9][10][11][12] PAHs were evaluated by the International Programme on Chemical Safety (IPCS), the Scientific Committee on Food (SCF) and by the Joint FAO/WHO Expert Committee on Food Additives (JECFA). SCF concluded that 15 Vol.…”
Section: Introductionmentioning
confidence: 99%
“…1 Thus, variable levels of PAHs have been reported in different food categories and beverages including vegetables and fruits, cereals, oils and fats, smoked products, coffee and tea. [2][3][4][5][6][7][8][9][10][11][12] PAHs were evaluated by the International Programme on Chemical Safety (IPCS), the Scientific Committee on Food (SCF) and by the Joint FAO/WHO Expert Committee on Food Additives (JECFA). SCF concluded that 15 Vol.…”
Section: Introductionmentioning
confidence: 99%
“…The most amount of benzo(a)pyrene was determined in instant coffee and in roasted coffee. It was shown that the content of benzo(a)pyrene depends on the roasting degree (Kayali-Sayadi et al, 1999;Badolato, et al, 2006). Typically, benzo(a)pyrene served as an indicator of the overall contamination of coffee with PAHs.…”
Section: Determination Of Polycyclic Aromatic Hydrocarbons (Pahs)mentioning
confidence: 99%
“…Statistical significance of these results was confirmed by t test with a p value of 0.05. For (Badolato et al 2006) Natural roasted coffee n.a. n.a.…”
Section: Real Sample Analysismentioning
confidence: 99%
“…The most popular extraction techniques are: Soxhlet extraction (Grover et al 2013;Badolato et al 2006) together with saponification (Lee and Shin 2010;Orecchio et al 2009;Kukare et al 2010), liquid-liquid extraction (LLE; Tfouni et al 2012Tfouni et al , 2013García-Falcón et al 2005;Bishnoi et al 2005), accelerated solvent extraction (Rey-Salgueiro et al 2009), and ultrasound-assisted extraction (Orecchio et al 2009;Ramalhosa et al 2009) using hexane, cyclohexane, dichloromethane, acetone, methanol, acetonitrile, ethyl acetate. Conventional cleanup strategies include solid-phase extraction (SPE) on cartridges with alumina, florisil, silica, C18, PS-DVB (Wieczorek et al 2002;Tfouni et al 2013;Lee and Shin 2010;Houessou et al 2005;García-Falcón et al 2005) or column chromatography with silica gel (Tfouni et al 2012;Grover et al 2013;Badolato et al 2006). For the detection and quantification of PAHs in coffee, gas chromatography with flame ionisation detector (Grover et al 2013), high performance liquid chromatography (HPLC) with photometric detection (Bishnoi et al 2005), fluorimetric detection (Tfouni et al 2012;Lee and Shin 2010;Houessou at el.…”
Section: Introductionmentioning
confidence: 99%